Teacher educators’ policy literacy of the deep learning approach: The curriculum design and practices - Mulyono, Herri; Ferawati, Ferawati (Universitas Jambi, Indonesia, 2026)
This qualitative case study examines how teacher educators' policy literacy shapes the integration of Indonesia's government-endorsed deep learning (DL) approach within Teacher Education Programs (TEPs). Through semi-structured interviews with six teacher educators from four private universities across Jakarta, Bandung, Jambi, and Palembang, the study investigated: (1) how EFL teacher educators conceptualize and demonstrate policy literacy regarding DL, (2) how they translate DL principles into curriculum design and pedagogical practice, and (3) what systemic and institutional barriers impede coherent integration. Thematic analysis of the interview data revealed a persistent policy-practice gap characterized by limited policy literacy, inconsistent pedagogical translation, and structural impediments. While participants demonstrated conceptual recognition of reform goals, their policy literacy remained superficial, lacking the interpretive capacity to operationalize DL principles effectively. Findings of the study show that effective curriculum reform requires transitioning from policy diffusion to pedagogical assimilation through sustained development of interpretive competence, collaborative sense-making platforms, and institutional scaffolding.